2017
DOI: 10.3389/fimmu.2017.00403
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Fas/FasL-Mediated Signal in Peripheral Immune Tolerance

Abstract: Fas-mediated apoptosis contributes to physiological and pathological cellular processes, such as differentiation and survival. In particular, the roles of Fas in immune cells are complex and critical for the maintenance of immune tolerance. The precise pathways and unique functions associated with Fas/FasL-mediated signaling in the immune system are known. The dual character of Fas/FasL-mediated immune regulation that induces beneficial or harmful effects is associated with the onset or development of immune d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
145
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 111 publications
3
145
1
1
Order By: Relevance
“…The negative correlation of oxygen saturation with Fas expression seems to confirm this hypothesis. Recently obtained data showing the pivotal role of the Fas/FasL signaling pathway in maintaining the homeostasis of immune system [6] supports the value of our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The negative correlation of oxygen saturation with Fas expression seems to confirm this hypothesis. Recently obtained data showing the pivotal role of the Fas/FasL signaling pathway in maintaining the homeostasis of immune system [6] supports the value of our study.…”
Section: Discussionsupporting
confidence: 88%
“…Fas (CD95) is a death receptor and belongs to the tumor necrosis factor receptor (TNFR) superfamily. Recently, its role in the modulation of immune response was described and it was found that the role of Fas/FasL pathway is wider than previously thought [4–6]. It was described, among others, that Fas/FasL signaling contributes to antigen-presenting cell activation, activation-induced cell death of T cells and thus to a maintenance of T cells homeostasis, Th17 differentiation, and precocious differentiation of memory T cells [4–6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed discrepancy might be due to the overlapping phenotypic marker to distinct DCs population [17]. Previous studies have shown that migratory DCs express different phenotypic markers during maturation and antigen presentation [35,44,45]. Surprisingly, we observed that CCR9 + DCs have immature phenotype as confirmed by reduced expression of MHC II and CD86, and increased expression of LAP and FasL.…”
Section: Discussioncontrasting
confidence: 61%
“…In the course of pregnancy modulation of immune response occurs to prevent pregnancy from rejection of allogenic graft. Immunomodulation could be connected to changes in apoptosis intensification and could cause lowering this processes [1][2][3][4]. In the course of pregnancy increase of vascular bed capacity and growing need of oxygen transporting molecules could cause slowing down apoptosis processes in bone marrow.…”
Section: Introductionmentioning
confidence: 99%